2017
DOI: 10.1016/j.clinthera.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Works in Progress: Update on Flavivirus Vaccine Development

Abstract: Most areas of the globe are endemic for at least one flavivirus, putting billions at risk for infection. This diverse group of viral pathogens causes a range of manifestations in humans from asymptomatic infection to hemorrhagic fever to encephalitis to birth defects and even death. Many flaviviruses are transmitted by mosquitos and have expanded in geographic distribution in recent years, with dengue virus being the most prevalent, infecting approximately 400 million people each year. The explosive emergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 194 publications
(215 reference statements)
0
95
0
1
Order By: Relevance
“…Protective vaccination can offer a long-term solution to mosquito transmitted viruses, and effective, widely available vaccines are commercially available for JEV and YFV. However, these viruses remain the exception, and commercial vaccines for the other viruses in these two genera are either not yet available 36 or of uncertain broad utility 37 . However, the number of viruses in question make it www.nature.com/scientificreports www.nature.com/scientificreports/ unlikely that vaccines will be developed for all the pathogenic viruses in these two genera, and the potential for the emergence of viruses not previously considered a significant pathogen of concern (as exemplified by the sudden emergence of ZIKV 11 ) suggests that a reliance on vaccination alone is not a viable long term solution.…”
Section: Discussionmentioning
confidence: 99%
“…Protective vaccination can offer a long-term solution to mosquito transmitted viruses, and effective, widely available vaccines are commercially available for JEV and YFV. However, these viruses remain the exception, and commercial vaccines for the other viruses in these two genera are either not yet available 36 or of uncertain broad utility 37 . However, the number of viruses in question make it www.nature.com/scientificreports www.nature.com/scientificreports/ unlikely that vaccines will be developed for all the pathogenic viruses in these two genera, and the potential for the emergence of viruses not previously considered a significant pathogen of concern (as exemplified by the sudden emergence of ZIKV 11 ) suggests that a reliance on vaccination alone is not a viable long term solution.…”
Section: Discussionmentioning
confidence: 99%
“…Flavivirus infections alone cause an estimated 200 million clinical cases worldwide. 54 Subsequent studies demonstrated broad-specificity against both mosquito-borne and TBEV serocomplex flaviviruses with low or no toxicity against the mammalian host cells. 55 No incorporation into human RNA or DNA was detected.…”
Section: Inhibition Of Viral Rna-dependent Rna Polymerasesmentioning
confidence: 99%
“…However, although it has been possible to develop efficient vaccinations for some members of the family (e.g. YFV, JEV), multiple factors are challenging the design of protective vaccination against WNV, DENV, and ZIKV . Among those, the viral variability has a considerable impact, and is particularly important in the case of DENV, where the co‐circulation of multiple serotypes with only 50%–60% homology leads to heterologous infections strongly associated with increased risk of severe DENV disease …”
Section: Importance Of T Cells In Flavivirus Vaccination: the Dengue mentioning
confidence: 99%